High perceived stress in patients on opioid agonist therapies during rapid transitional response to the COVID-19 pandemic in Ukraine - Samy J. Galvez; Frederick L. Altice; Frederick L. Altice; Frederick L. Altice; Anna Meteliuk; Roman Ivasiy; Eteri Machavariani; Scott O. Farnum; Tetiana Fomenko; Zahedul Islam; Lynn M. Madden; Lynn M. Madden (Frontiers Media S.A., 2023)
BackgroundThe COVID-19 pandemic resulted in marked disruptions in healthcare delivery in Ukraine related to emergency guidance in response to treating opioid use disorder (OUD). Patients with OUD, a group with high levels of comorbid medical and psychiatric disorders, and prescribed opioid agonist therapies (OAT) were rapidly shifted to take-home dosing if they were deemed clinically stable. The impact of these shifts on patient stress and related substance use during the pandemic, however, is unknown.MethodsIn early May 2020, 269 randomly selected OAT patients in Ukraine were surveyed to assess their stress level and substance use using the validated Perceived Stress Scale and examined correlates of severe perceived stress.ResultsOverall, 195 (72.5%) met criteria for moderate to severe levels of stress, which was independently correlated with having started OAT within the past 12 months (aOR: 1.33; 95%CI: 1.15-1.55), living in a large metropolitan area (aOR: 1.31; 95%CI: 1.18-1.46), having been asked by others to share their medication (aOR: 1.13; 95%CI: 1.02-1.25), and having an increase of over 10 min in transportation time to get to treatment (aOR: 1.16; 95%CI: 1.04-1.29). Twenty seven (10%) patients felt at high risk of relapse, while 24 (8.9%) patients reported purchasing drugs.ConclusionDuring a time of great uncertainty soon after emergency guidance to the COVID-19 pandemic, there was extraordinary high levels of perceived stress reported. In response to emergency guidance, OAT patients should be screened for perceived stress and certain subgroups should be targeted for additional psychosocial support.